Electrical Heating Vest for Heart Failure and/or Hypertension Therapy - Meng, Fanqin (Université d'Ottawa / University of Ottawa, 2017)
Purpose: To develop a lightweight, safe, and controllable electrical heating vest for heart failure and/or hypertension patients. Methods: a. A literature review related to the topic was conducted. b. A model of a simplified human body thermoregulation system was developed and simulated. It was used to predict the power requirement of the battery to increase core body temperature up to 1 Celsius degree (°C). c. A prototype with a smart controller was developed d. In-vitro tests of the prototype were conducted to assess performance and safety. e. The prototype was tested on 10 healthy human volunteers and the results were analyzed. Results: a. An average core body temperature increase of 0.3 °C (P<0.05) was observed in healthy human volunteer tests within 30 minutes. b. The vest induced decreases in systolic blood pressure of 5.5 mmHg and diastolic blood pressure of 4.8 mmHg on average. Conclusions: A carbon-fiber vest can increase body core temperature by 0.3°C lowering systolic and diastolic blood pressure, which can be potentially used for helping heart failure and/or hypertension patients.
Keywords: Thermal Therapy; Electrical Heating Vest; Heart Failure; Hypertension